A Forest of Machines : gli ambienti biosemiotici di Pierre Huyghe - Tolfo, Davide (Scenari, 2021)
mwelt, After Alife Ahead or Untilled, show an idea of art made from the relationship between inanimate objects and living beings – animals, bacteria, plants. Visitors of his work Untilled, set in Auerpark for DOCUMENTA13, find themselves in an environment rather than being the spectators of an installation: a female statue with her face covered by a giant beehive, a white dog with a pink paw, medical and hallucinogenic plants and an oak taken from Joseph Beuy’s work 7000 Eichen are only few of the elements that compose it. The visitor is never the main actor in the artistic practice of Pierre Huyghe. Instead, the key role is played by the network of relationships that make the work a living organism – a biosemiotic environment like the artist says. I believe this concept can give a positive answer to the contemporary question “Is it possible to make art in the Anthropocene?”. In the first part of this essay I show the problematic distinction between the concepts of visitors and exhibition places in Pierre Huyghe’s art. Starting from this issue, I try to analyze how works like Human Mask and The Host and the Cloud deconstruct universal paradigms that define identity and humanity. In the main part of this work, I focus on the idea of biosemiotic artwork, showing four different examples of compositions where natural and cultural elements mingle, overcoming their split. Finally, by means of the Object Oriented Ontologies, I show how much Pierre Huyghe’s work can be useful to think beyond anthropocentrism, or, in other words, to create a posthuman practice.